Customer Loyalty: The Difference between Full-Service Carriers and Low-Cost Carriers in Indonesia - Yasintha Soelasih; Sumani Sumani (Binus Business Review, 2021)
The level of competition in the aviation industry has increased since the regulation change in 1999. Aviation companies in providing services can be divided into three categories: full service, medium service, and no-frills service. Both Full-Service Carriers (FSCs) and Low-Cost Carriers (LCCs) experience a high level of competition. The research aimed to look at the differences in customer loyalty on domestic FSCs and LCCs in Indonesia. The differences were shown from testing the effect of service quality on customer loyalty mediated by customer satisfaction and behavioral intention to use. Respondents were FSCs and LCCs passengers. Samples were taken by purposive sampling. There were 522 respondents for FSCs and 529 respondents for LCCs were observed by distributing questionnaires. Then, the research tested the validity and reliability of the variables using Confirmatory Factor Analysis (CFA), Composite Reliability (CR), and Average Variance Extracted (AVE). Structural Equation Modeling (SEM) was also applied to examine the hypothesis. The results show the formation of customer loyalty from service quality, customer satisfaction, and behavioral intention to use on FSCs and LCCs. The most significant factor is the behavioral intention in forming customer loyalty in FSCs and LCCs. Meanwhile, customer satisfaction does not influence customer loyalty for FSCs and LCCs.